2015
DOI: 10.1136/gutjnl-2014-307671
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 fosters HCC development by enhancing TGF-β-mediated alternative activation of macrophages

Abstract: Tim-3 displays critical roles in microenvironment-induced activation and protumoral effects of TAMs in HCC. Interference of Tim-3 might be great potential in HCC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
258
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(271 citation statements)
references
References 37 publications
9
258
2
2
Order By: Relevance
“…Blockade of TIM-3 in T cells cultured in vitro restored proliferation and IL-2 and IFN-γ production [9]. Recently, Yan et al showed that TIM-3 is highly expressed by monocytes and macrophage in HCC patients [46]. TIM-3 expression in macrophage was enhanced by TGF-β stimulation.…”
Section: Tim-3mentioning
confidence: 99%
“…Blockade of TIM-3 in T cells cultured in vitro restored proliferation and IL-2 and IFN-γ production [9]. Recently, Yan et al showed that TIM-3 is highly expressed by monocytes and macrophage in HCC patients [46]. TIM-3 expression in macrophage was enhanced by TGF-β stimulation.…”
Section: Tim-3mentioning
confidence: 99%
“…Of note, the role of Tim-3 in natural immunity is much more complex than its role in adaptive immunity. Recently, our laboratory has found that Tim-3 regulate the polarization of macrophages and accelerate the transformation of M1 macrophages into M2 macrophages, which then suppress the inflammatory response in HCC [44] . Together, these data indicate the complicated role of Tim-3 in regulating innate immune cells.…”
Section: Tim-3 and Monocytes/macrophagesmentioning
confidence: 99%
“…Specifically, elevated Tim-3 expression is negatively associated with tumor grade and patient survival. Moreover, ectopic expression of Tim-3 induces altered M2 activation, with a phenotype that promotes tumor development [44] . Our results further emphasize the critical role of Tim-3 as a new component in HCC progression.…”
Section: Tim-3 and Hccmentioning
confidence: 99%
“…TIM-3 is an immune receptor discovered in 2002 that is expressed on a variety of immune cells including dendritic cells, macrophages, and T cells 20-22 . TIM-3 mediates its suppressive activity on immune cells via its ligands that include phosphatidylserine, CEACAM-1 and the widely expressed ligand galectin-9 23,24 .…”
Section: Introductionmentioning
confidence: 99%